Conversion of Thioamide to Benzothiazole with Oxidizing Agents - Lee, Do-Hun (Asian Journal of Chemistry, 2014)
In order to search for novel chemotherapeutical agents, we tried reactions of lutidine(s) with active methyl group and anilines in the presence of sulfur and we report synthesis of amide from thioamide by using SeO2, ZrO2 or KMnO4. Benzothiazoles was formed by the oxidative cyclization of thioamides with oxidizing agent (SeO2, ZrO2 and KMnO4) in an alkaline solution. We know reactivity of SeO2 as an oxidizing agent is higher than that of ZrO2 and KMnO4.